Kaj izvira iz jezikovnih virov - Vintar, Špela (Jezik in slovstvo, 2003)
Lanugage resources such as corpora, lexica and thesauri as well as basic language analysis tools are needed on the one hand for linguistic description and the production of reference works, and on the other hand for the development of various user applications. The paper describes some areas of exploting language resources for linguistic and other purposes from the user's perspective. The overview begins with corpus-based methods in lexicography, grammar and translation studies, then we briefly list some better-known technologies such as spell-checker, thesauri and machine translation tools. In recent years the field is increasingly focussing on semantic applications for Document Classification and Summarization, Information Retrieval and Ontology Building. The second part of the paper presents two specific fields of exploiting language resources: Automatic Term Extraction and Knowledge Discovery in the medical domain through Text Mining.
Keywords: Slovene; slovenščina; leksikografija; lexicography; Corpus linguistics; korpusno jezikoslovje; Language technology; jezikovne tehnologije